Implementasi Metode Promethee Dan Borda Dalam Sistem Pendukung Keputusan Pemilihan Lokasi Pembukaan Cabang Baru Bank - Apriliani, Dyah; Adi, Kusworo; Gernowo, Rachmat (JSINBIS (Jurnal Sistem Informasi Bisnis), 2015)
The selection of a new branch bank location is crucial to the success of the bank in the future. The object of this research is BMT Muamalat. PROMETHEE method is used to manage individual decision of each decision makers, while Borda method is used to manage group decisions of PROMETHEE method in ranking the results. The use of these two methods is one solution to produce a more objective group decision. Ranked of alternative location have appropriated with the opening rules of the new branches of BMT Muamalat. As for the variables in this study are criminality, facilities and infrastructures, per capita income, economic growth, population, and the number of competitors around the alternative location of a new branch. The results of this research is Banyuputih as the best alternative location.Â Â